Reproduction Method of Rockfall Geologic Hazards Based on Oblique Photography and Three-Dimensional Discontinuous Deformation Analysis - Fu, Xiaodong; Ding, Haifeng; Sheng, Qian; Chen, Jian; Chen, He; Li, Guo; Fang, Liuyang; Du, Wenjie (Frontiers in Earth Science, 2021)
Rockfall geologic hazards are widely distributed. Due to their concealed nature, rockfalls are difficult to investigate using traditional contact survey methods, and the hazards they pose affect major projects and people’s safety. Reproducing methods, including scene survey and movement process analysis, are primary tasks used to prevent these hazards; however, few reconstruction methods can directly apply the parameters of the rockfall geologic hazards obtained by the scene survey to evaluate the movement process. To address this problem, a method of reproduction based on oblique photography and three-dimensional discontinuous deformation analysis (3D-DDA) is proposed; the method consists of three key techniques (oblique photography, 3D rock block system modeling, and 3D rock block system analysis). First, geometric characteristic parameters of the terrain, rockfall, and discontinuities are extracted based on oblique photography using an unmanned aerial vehicle (UAV). Second, the block system model of rockfall is reconstructed by using 3D computational geometry theory and taking these geometric characteristic parameters as an input. Finally, the whole evolution process of rockfall geologic hazard, including initiation, movement, and accumulation, is simulated by the 3D-DDA method. To verify the practicability of this reproduction method, a typical rockfall geologic hazard, located in the K8 + 050 section of the Gaohai expressway, Yunnan, China, is studied. In addition, the characteristics of 19 dangerous rock masses in the survey area are clarified, and the geometric features of the discontinuities in the rock masses are extracted based on oblique photography using an UAV. The block system model of a potential rockfall is reconstructed, the movement trajectory is simulated by the 3D-DDA method, and the evolution process of velocity and kinetic energy of the rockfall verifies that the spatial layout of the current three-level passive protective nets system is reasonable. The case study indicates that the proposed method provides a geological and mechanical model for the risk assessment of rockfall geologic hazards.